Rumination, gender, and depressive symptoms associated with caregiving strain in bipolar disorder. - Perlick, D; Gonzalez, J; Michael, L; Huth, M; Culver, J; Kaczynski, R; Calabrese, J; Miklowitz, D (2012)
OBJECTIVE: To evaluate the associations between indices of caregiving strain, ruminative style, depressive symptoms, and gender among family members of patients with bipolar disorder. METHOD: One hundred and fifty primary caregivers of patients enrolled in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) participated in a cross-sectional study to evaluate the role of ruminative style in maintaining depressive symptoms associated with caregiving strain. Patient lifetime diagnosis and current episode status were evaluated by the Affective Disorder Evaluation and the Clinical Monitoring Form. Caregivers were evaluated within 30 days of the patient on measures of family strain, depressive symptoms, and ruminative style. RESULTS: Men and women did not differ on depression, caregiver strain, or ruminative style scores. Scores suggest an overall mild level of depression and moderate caregiver strain for the sample. Greater caregiver strain was significantly associated (P<0.05) with rumination and level of depressive symptoms, controlling for patient clinical status and demographic variables. Rumination reduced the apparent association between strain and depression by nearly half. Gender was not significantly associated with depression or rumination. CONCLUSION: Rumination helps explain depressive symptoms experienced by both male and female caregivers of patients with bipolar disorder. Interventions for caregivers targeted at decreasing rumination should be considered.